Development and Validation of an Empirical Dietary Inflammatory Index - Tabung, Fred K; Smith-Warner, Stephanie A; Chavarro, Jorge E; Wu, Kana; Fuchs, Charles S; Hu, Frank B; Chan, Andrew T; Willett, Walter C; Giovannucci, Edward L (The Journal of nutrition, 2016)
Knowledge on specific biological pathways mediating disease occurrence (e.g., inflammation) may be utilized to construct hypotheses-driven dietary patterns that take advantage of current evidence on disease-related hypotheses and the statistical methods of a posteriori patterns. We developed and validated an empirical dietary inflammatory index (EDII) based on food groups. We entered 39 pre-defined food groups in reduced rank regression models followed by stepwise linear regression analyses in the Nurses' Health Study (NHS, n = 5230) to identify a dietary pattern most predictive of 3 plasma inflammatory markers: interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor α receptor 2 (TNFαR2). We evaluated the construct validity of the EDII in 2 independent samples from NHS-II (n = 1002) and Health Professionals Follow-up Study (HPFS, n = 2632) using multivariable-adjusted linear regression models to examine how well the EDII predicted concentrations of IL-6, CRP, TNFαR2, adiponectin, and an overall inflammatory marker score combining all biomarkers. The EDII is the weighted sum of 18 food groups; 9 are anti-inflammatory and 9 proinflammatory. In NHS-II and HPFS, the EDII significantly predicted concentrations of all biomarkers. For example, the relative concentrations comparing extreme EDII quintiles in NHS-II were: adiponectin, 0.88 (95% CI, 0.80, 0.96), P-trend = 0.003; and CRP, 1.52 (95% CI, 1.18, 1.97), P-trend = 0.002. Corresponding associations in HPFS were: 0.87 (95% CI, 0.82, 0.92), P-trend < 0.0001; and 1.23 (95% CI, 1.09, 1.40), P-trend = 0.002. The EDII represents, to our knowledge, a novel, hypothesis-driven, empirically derived dietary pattern that assesses diet quality based on its inflammatory potential. Its strong construct validity in independent samples of women and men indicates its usefulness in assessing the inflammatory potential of whole diets. Additionally, the EDII may be calculated in a standardized and reproducible manner across different populations thus circumventing a major limitation of dietary patterns derived from the same study in which they are applied.